How Has the Secret Garden of Politics Changed in Italy (1994-2015)?. (June 2016) - Cerruto, Maurizio; Facello, Chiara; Raniolo, Francesco
The goal of this article is to assess changes in the candidate selection methods in Italy starting from elections of 1994, when the selection process dominated by party has failed, and new recruitment techniques emerged both at national and regional level. This article provides an overview of intraparty candidate selection methods occurring at two levels analyzing formal rules and survey data on attitudes held by middle-level party elite (national) and councilors (regional). Has there been a real democratization (in terms of more inclusiveness and more decentralization) of the candidates' selection? How effective is the selection process on gender representation? The findings show that national elite has a strong hold on party recruitment despite the introduction of democratic procedures in the candidate selection for public office and leadership of some parties; at regional level, individual representation acquires a powerful role in comparison with party representation.